Influence of corporate social responsibility considering dual-channel recycling competition and privacy information protection. (1st November 2022) - Huang, Yanting; Liang, Yuqing
Abstract: When conducting transactions of recycling, consumers are now paying more attention to information security, concerning the problem of information leakage. From this perspective, we aim to testify whether constructing offline stores combined with privacy information protection to guarantee information security is worthwhile, and what is the effects of Corporate social responsibility (CSR) on profits of competing companies with dual-channel recycling. We build up models to examine the effects of the offline store construction integrated with privacy information protection on profits of companies. Moreover, we construct several models with the total utility of the enterprise to further evaluate the effect of CSR, which composes of the net profit and the CSR utility under different CSR consideration. The CSR is taken by no entities, only entity with offline channel, only entity with online channel and both entities, respectively. The results show the competing companies could gain the most earnings in the situation that both channels consider CSR, while only the offline channel considers CSR is the worst choice. In addition, the revenue-sharing contract and cost-sharing contract could optimize the profit of enterprise constructing privacy information protection, and the former is better than the latter. This study gives insights into the construction of privacy information protection and the consideration of CSR activities of enterprises, which in turn help boost the recycling process and achieve environmentally sustainable of the recycling industry. Highlights: Study the impact of information security protection on enterprise. Research recycling competition in offline and online channel of recycling companies. Evaluate CSR activities from the perspective of the profits and social welfare. Obtain the optimal contract for the enterprise to collaborate with opponents.